2021
DOI: 10.1039/d0an02403a
|View full text |Cite
|
Sign up to set email alerts
|

ANFO vapour detection with conducting polymer percolation network sensors and GC/MS

Abstract: Ammonium nitrate mixed with fuel oil (ANFO) is commonly used in improvised explosive devices (IEDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The conductivity of the whole percolation pathway can be disrupted by the analyte on polymer connections, while the analyte will only affect the local surface conductivity of the dense thin film. Our previous work has shown that electropolymerization can be used to fabricate chemiresistors based on polypyrrole (PPy) and poly­(3,4-ethylenedioxythio-phene) (PEDOT) percolation networks and that the sensitivities and limits of detection of the resulting percolation networks to ammonia, nitrogen dioxide, and ammonium nitrate/fuel oil are significantly improved compared to more traditional thin-film chemiresistive sensors. …”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of the whole percolation pathway can be disrupted by the analyte on polymer connections, while the analyte will only affect the local surface conductivity of the dense thin film. Our previous work has shown that electropolymerization can be used to fabricate chemiresistors based on polypyrrole (PPy) and poly­(3,4-ethylenedioxythio-phene) (PEDOT) percolation networks and that the sensitivities and limits of detection of the resulting percolation networks to ammonia, nitrogen dioxide, and ammonium nitrate/fuel oil are significantly improved compared to more traditional thin-film chemiresistive sensors. …”
Section: Introductionmentioning
confidence: 99%
“…Lefferts, M.J., et al used “ANFO chemiresistive vapour sensors based on polypyrrole (PPy) percolation networks to enhance” GC-MS results and reported improved sensitivity over thin film and detected “13–180 ppb of ammonia emitted by a variety of different ammonium nitrate …” mixtures [ 656 ].…”
Section: General Detectionmentioning
confidence: 99%
“…Conducting polymers have also been heavily investigated for chemiresistive sensing at room temperature, however they have issues such as signal drifts and lack of stability over time. [29][30][31][32] Therefore, there is a need for robust and easily miniaturized room temperature sensing materials for application in chemiresistive gas sensing.…”
Section: Introductionmentioning
confidence: 99%